2019
DOI: 10.3390/polym11101714
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant and Anti-Diabetes Potential of Water-Soluble Chitosan–Glucose Derivatives Produced by Maillard Reaction

Abstract: Chitosan-sugar derivatives demonstrate some useful biology activities (for example anti-oxidant and anti-microbial activities). In this study, water-soluble chitosan–glucose derivatives (WSCGDs) were produced from a water-soluble chitosan hydrochloride (WSC) with 12.5 kDa of molecular weight and 24.05% of degree of acetylation (DA) via Maillard reaction with the heating temperatures of 100 °C and 121 °C. The Maillard reaction between WSC and glucose was investigated by measuring the absorbances at 420 nm and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…It occurs abundantly in the exoskeleton of arthropods, the gladius of squid, and the cell walls of fungi [ 2 , 3 ]. Chitin and its derivatives have been used in many fields; for instance, environmental treatment, agriculture, medicine, and food [ 4 , 5 , 6 , 7 , 8 ]. Chitinous fishery by-products, such as shrimp heads, shrimp shells, crab shells, and squid pens are the major sources for chitin and chitosan preparations [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs abundantly in the exoskeleton of arthropods, the gladius of squid, and the cell walls of fungi [ 2 , 3 ]. Chitin and its derivatives have been used in many fields; for instance, environmental treatment, agriculture, medicine, and food [ 4 , 5 , 6 , 7 , 8 ]. Chitinous fishery by-products, such as shrimp heads, shrimp shells, crab shells, and squid pens are the major sources for chitin and chitosan preparations [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal pH for Paenibacillus sp. TKU047 chitosanase activity was determined by adding the enzyme into substrate solutions at different pH (3)(4)(5)(6)(7)(8)(9)(10)(11). The pH stability of the enzyme of Paenibacillus sp.…”
Section: Effects Of Temperature and Phmentioning
confidence: 99%
“…Chitosan is a linear polymer that is produced from chitin via the deacetylation process [ 1 ]. Chitosan comprises some excellent properties including non-toxicity, adsorption, biocompatibility, and biodegradability, thus, it can potentially be used in many fields such as medicine, wastewater treatment, agriculture, and functional food [ 2 , 3 , 4 , 5 , 6 , 7 ]. One of the most challenging applications of chitosan is its poor solubility in a neutral aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also use the ratio of A 294 /A 420 to evaluate the extent of the Maillard reaction. The increased A 294 /A 420 indicates the intermediate stage, while the decreased A 294 /A 420 indicates the final stage of the reaction [ 16 , 74 ]. During the Maillard reaction, fluorescent compounds (the intermediates) are also developed and recognized as the precursors of the brown compounds [ 3 , 81 , 82 ].…”
Section: Preparation and Identification Of Chitosan-based Maillardmentioning
confidence: 99%
“…The fluorescence intensity was measured at an excitation wavelength of 346 nm and emission wavelength of 415 nm on a fluorescence spectrophotometer [ 83 ]. Studies showed that the increased fluorescence intensity of the mixtures suggesting the CMRPs formation and decreased fluorescence ability observed during the reaction suggesting the final stage of the formation of CMRPs [ 70 , 74 ].…”
Section: Preparation and Identification Of Chitosan-based Maillardmentioning
confidence: 99%